HYBRID WORK IN EMERGING ECONOMIES: A PRISMA-GUIDED REVIEW OF HRM PRACTICES AND PERFORMANCE IMPACTS - Mochammad Isa Anshori; Siti Nur Eliza Rahmawati (Adisam Publisher, 2025)
This study aims to examine Human Resource Management (HRM) practices in the context of hybrid work in developing countries and their impact on organizational performance and innovation. Using a literature review guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) protocol, this study identified, filtered, and analyzed relevant literature related to the implementation of hybrid work. The results indicate that hybrid work offers strategic opportunities for increasing flexibility, productivity, and work-life balance, but also poses challenges in terms of coordination, performance management, and employee well-being. HRM plays a crucial role in designing adaptive policies, creating relevant performance-based evaluation systems, and building an inclusive work culture. These findings confirm that the successful implementation of hybrid work in developing countries is heavily influenced by technological readiness, leadership quality, and HRM policies that are responsive to the dynamics of the modern work environment. This study provides a theoretical contribution by enriching the literature on HRM practices in the hybrid work era, while also offering practical implications for organizations in developing countries in formulating sustainable HR management strategies.